Synthesis, properties, and two-dimensional adsorption characteristics of 5-amino[6]hexahelicene - Van der Meijden, Maarten W.; Gelens, Edith; Murillo-Quirós, Natalia; Fuhr, Javier D.; Gayone, Esteban; Ascolani, Hugo; Wurst, Klaus; Lingenfelder, Magalí; Kellogg, Richard M. (Willy, 2016)
A convergent synthesis of racemic 5-amino[6]hexahelicene is described. Cross-coupling reactions are used to assemble a pentacyclic framework, and a metal-catalyzed ring-closure comprises the final step. The enantiomers were separated by means of chromatography and the absolute configurations were assigned by comparison of the CD spectra with hexahelicene. The t1/2 value for racemization at 210 8C was approximately 1 hour. Scanning tunneling microscopy (STM) measurements were carried out on enantiopure and racemic samples of aminohelicene on Au(111) under ultrahigh vacuum (UHV) conditions.
Artículo
Keywords: 5-amino [6] hexaheliceno; STM; UHV; Research Subject Categories::NATURAL SCIENCES::Chemistry; Cromatolografía